2012
DOI: 10.1002/hep.25741
|View full text |Cite
|
Sign up to set email alerts
|

Higher dietary fructose is associated with impaired hepatic adenosine triphosphate homeostasis in obese individuals with type 2 diabetes

Abstract: Fructose consumption predicts increased hepatic fibrosis in those with nonalcoholic fatty liver disease (NAFLD). Due to its ability to lower hepatic adenosine triphosphate (ATP) levels, habitual fructose consumption could result in more hepatic ATP depletion and impaired ATP recovery. The degree of ATP depletion following an intravenous fructose challenge test in low versus high fructose consumers was assessed. We evaluated diabetic adults enrolled in the Look AHEAD Fatty Liver Ancillary Study (n=244) for whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
144
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 39 publications
8
144
0
2
Order By: Relevance
“…Accordingly, other mechanisms must account for the association between hyperuricemia and insulin resistance. Diet-induced insulin resistance is a possible explanation for the association between serum urate and insulin resistance (1,5). During consumption of high-carbohydrate diets, the liver is exposed to high portal vein concentrations of glucose and/or fructose, which cause elevation in hepatic organic phosphate esters and activation of the transcription factor ChREBP-Mlx (3,6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, other mechanisms must account for the association between hyperuricemia and insulin resistance. Diet-induced insulin resistance is a possible explanation for the association between serum urate and insulin resistance (1,5). During consumption of high-carbohydrate diets, the liver is exposed to high portal vein concentrations of glucose and/or fructose, which cause elevation in hepatic organic phosphate esters and activation of the transcription factor ChREBP-Mlx (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…1). However, whether dietary fructose contributes to hyperuricemia in liver disease remains debated (1,33,40).Studies in humans have reported low hepatic ATP in obesity (10) and inverse correlations between hepatic steatosis or hepatic insulin resistance and hepatocellular P i or ATP levels (32). Accordingly, compromised hepatic P i or ATP homeostasis is a possible link between NAFLD and hyperuricemia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…All these mechanisms initially triggered by the transport of fructose into the hepatocyte are extremely relevant and contribute to the development of diseases such as hyperglycaemia, gout, endothelial inflammation and arterial hypertension [2,31].…”
Section: Sweet Poisonmentioning
confidence: 99%